Between You and I: A Methodological, Mixed-method Corpus-pragmatic Approach to Hypercorrect Uses of Subject Pronouns in Object Position - Kirner-Ludwig, Monika; Oberhofer, Kathrin; Heiss, Julia (Corpus pragmatics : international journal of corpus linguistics and pragmatics, 2023)
The present paper takes a corpus-pragmatic approach to an issue traditionally situated at the interface of sociolinguistics, grammatical prescriptivism and syntax: the use of the hypercorrect structures <X and I> and <I and X> in object position and British and American English speakers’ usage of such pronoun binomials as prestige constructions. Here, we dedicate significant space to the meta-methodological level pertaining to the corpus-linguistic challenges entailed in systematically identifying relevant occurrences of coordinated noun phrases that feature at least one nominal component unambiguously case-marked. We use a self-compiled corpus of 14,165,810 words of transcribed telecinematic discourse in order to not only establish the extent of any hypercorrect usage, but also to see it in relation with unmarked and both grammatically correct and incorrect uses of the subject and object forms.